Analisis Internalisasi Nilai Institusional IDEAL di Politeknik Caltex Riau - Lailanisa Fadlilani; Roni Setia Nugraha; Zainal Arifin Renaldo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research aims to analyze the internalization of IDEAL (Integrity, Dignity, Excellence, Agility, and Loyalty) institutional values within the Caltex Riau Polytechnic (PCR) and identify challenges and opportunities to strengthen them through organizational communication. The IDEAL value has been established as the foundation of organizational culture since it was listed in the 2023 Institutional Statute and has become a reference for the behavior of the academic community. This study uses a descriptive qualitative approach with observation techniques, in-depth interviews, and analysis of institutional documents. The results of the study show that the value of IDEAL has been integrated in official documents and formal activities of the institution. Lecturers and employees show a relatively consistent internalization of values through work practices, even though they are not supported by measurable behavioral indicators. Meanwhile, at the student level, the internalization of values is still at the introduction stage and is symbolic. The research also found irregularities in communication between units and the use of digital media that have not been managed strategically. These findings confirm the need for a structured, participatory, and adaptive value communication system for the digital ecosystem to strengthen the overall internalization of IDEAL values.